GAMBARAN PENGETAHUAN IBU HAMIL TENTANG ASI EKSKLUSIF (UPPM. Poltekkes Kemenkes Bandung, 2021)
ABSTRACT This research is motivated by the causes of IMR (Infant Mortality Rate). The biggest direct causes of infant mortality during 2018 are LBW 14%, pneumonia 13.2%, diarrhea 17.2%, hyperbilirubin 3%, nutritional deficit 3%, sepsis 22%, congenital abnormalities 4.9%, tetanus 1.5% , Sepsis, respiratory distress syndrome 14% and unknown cause 5.5%. One of the factors that play a role in this high IMR is the period of baby growth and development of 0-6 months requires nutritional intake obtained through exclusive breastfeeding. Factors that can reduce IMR themselves are nutrient factors found in breast milk guarantee good nutritional status and reduce morbidity and mortality of children.Exclusive breastfeeding is only breastfeeding for infants up to 6 months of age without the addition of fluids or other foods. Growth disorders at the beginning of a baby's life are caused by the mother not giving exclusive breastfeeding to her baby. This is of course closely related to the low coverage of exclusive breastfeeding. For this reason, pregnant women need knowledge about exclusive breastfeeding, so this research aims to find out the description of the knowledge of pregnant women about Exclusive ASI. The method used is a systematic literature review. Secondary data collection techniques with 3 research journals. Literature review results from the three research journals show that based on the knowledge of respondents in the results of journal 1 research that is the level of sufficient knowledge as much (65%), the results of the 2nd journal are quite knowledgeable as much as (60.4%) and the results of the third journal good knowledgeable average (76.2%). It can be concluded that the description of pregnant women about Exclusive ASI is categorized as having sufficient knowledge, this is influenced by education and information. Recommendations to health care institutions to streamline promotive action. One way to do this is to provide counseling on exclusive breastfeeding to pregnant women in the Puskesmas target area. Thus pregnant women understand about the importance of exclusive breastfeeding for babies. Key words: Exclusive breastfeeding, Knowledge, Pregnant women